Process Intensification as Game Changer in Enzyme Catalysis - Burek, Bastien O.; Dawood, Ayad W. H.; Hollmann, Frank; Liese, Andreas; Holtmann, Dirk (Frontiers in Catalysis, 2022)
Enzyme catalysis, made tremendous progress over the last years in identification of new enzymes and new enzymatic reactivity’s as well as optimization of existing enzymes. However, the performance of the resulting processes is often still limited, e.g. in regard of productivity, realized product concentrations and the stability of the enzymes. Different topics (like limited specific activity, unfavourable kinetics or limited enzyme stability) can be addressed via enzyme engineering. On the other hand, there is also a long list of topics that are not addressable by enzyme engineering. Here typical examples are unfavourable reaction thermodynamics, selectivity in multistep reactions or low water solubility. These challenges can only be addressed through an adaption of the reaction system. The procedures of process intensification (PI) represent a good approach to reach most suitable systems. The general objective of PI is to achieve significant benefits in terms of capital and operating costs as well as product quality, waste, and process safety by applying innovative principles. The aim of the review is to show the current capabilities and future potentials of PI in enzyme catalysis. The focus of the paper is on alternative methods of energy input, innovative reactor concepts and reaction media with improved properties.